418 A Delphi process to determine clinicians' attitudes and beliefs towards paediatric major incident triage within the United Kingdom. (17th August 2022) - Vassallo, James; Blakey, Sarah; Cowburn, Philip; Surridge, Julia; Smith, Jason; Scholefield, Barney; Lyttle, Mark
Abstract : Aims: Triage is a key principle in the effective management of major incidents, yet there is a paucity of evidence surrounding the optimal method of paediatric major incident triage (MIT). This study aimed to derive consensus on key components of paediatric MIT among healthcare professionals involved in the management of paediatric major incidents. Methods: This modified two-round online Delphi consensus study, delivered between July and October 2021, included participants from pre-hospital and hospital specialities involved in managing a paediatric major incident. Statements were derived iteratively based on review of MIT tools, and extant literature. A 5-point Likert agreement scale was used to determine consensus, which was set a priori at 70%. Results: 111 clinicians completed both rounds, with 13 of 17 statements reaching consensus. Positive consensus was reached on the use of rescue breaths in mechanisms associated with hypoxia or asphyxiation, use of mobility assessment as a crude discriminator of injury, and use of adult physiology for older children. Whilst positive consensus was reached on the benefits of a single MIT tool for use across the entire adult and paediatric age range, there was negative consensus in relation to the clinical implementation of such a tool. Consensus could not be reached regarding the use of a single tool across the whole paediatric age range specifically, nor on the use of rescue breaths in blunt or penetrating trauma. Conclusion: This Delphi study has established consensus among a large group of subject matter experts on several key elements of paediatric MIT. Further work is required to develop a triage tool that can be implemented based on emerging and ongoing research, and which is acceptable to clinicians.